Hallazgos en ultranografía en pacientes diabéticos tipo 2. - Romero Calero, Sara Paola (2014)
This research is descriptive and transversal whose overall objective is to determine the most frequent pathological findings diagnosed by ultrasound and ocular blood flow changes in patients with type 2 diabetes who attended the Regional Hospital of the Ecuadorian Institute of Social Security, Manuel Ygnacio Monteros Loja, in the period from October to December 2013 66 eyes sonography was performed in B mode and Doppler mode in 60 eyes, referral service outpatient departments of Internal Medicine and Ophthalmology. The ages of the patients understood between 40 and 72 years (64% were older than 65 years). It also noted that 88% were female and 12% male. The most common eye diseases found in type 2 diabetic patients diagnosed by ultrasound vitreous degeneration was found in 45% (35 eyes), cataract in 26% (20 eyes), farsightedness 6% (5 eyes), myopia, 5% (eyes), vitreous hemorrhage to 5% (4 eyes), posterior vitreous detachment to 5% (eyes), Pseudoafaquia 3% (2 eyes), retinal detachment 3% (2 eyes), staphyloma 1% (1 eye) and hyalosis asteroid 1% (1 eye) In the classification of ocular pathologies according to eye topography we need the most affected part was the glass with 51% (28 eyes), followed by the crystal with 28% (22 eyes), abnormal eye size with 13 % (10 eyes), posterior vitreous with 5% (4 eyes) and retinal 3% (2 eyes) Doppler evaluation of the AO found that the VPS were found decreased in 42 eyes (70%), likewise the VFD evidenced decreased in 39 eyes (65%) with values of 2.73 + 2.6. The IR was elevated in 57% (34 eyes) with values of 1 + 0.08. ACR was observed in the VPS he was decreased in 24 eyes (40%), with an average of 6.86 and a SD of + 1. Evidenced in the VFD decreased in 80% (48 eyes) with values of 1 + 1.2. The IR was elevated in 83% (50 eyes) with values of 1 + 0.08. Ocular ultrasound is very sensitive for the diagnosis of ocular pathology, being easy to perform and completely safe noninvasive technique also allows us to assess the state of the ocular vasculature in order to determine the hemodynamic characteristics of the blood vessels, taking into that diabetes is a disease that causes predominant involvement of microcirculation.